Measuring What Matters: India's Draft National Health Research Policy (2026) puts patient outcomes over publication metrics - Punnya V. Angadi (Indian Journal of Health Sciences and Biomedical Research KLEU, 2026)
For years, success in Indian health research meant papers, citations, and patents. However, this rarely meant better outcomes for patients. India's Draft National Health Research Policy, 2026, proposes a fundamental shift in how research success is defined and attempts to close this gap. In this editorial, the main elements of the policy, such as proposing the ICMR Impact of Research and Innovation Scale (ICMR-IRIS), reformed research infrastructure, and a National Health Research Agenda shaped by real population needs rather than publishing convenience, are discussed. These components are placed in the context of a broader global shift towards responsible research evaluation. The policy's foundational philosophy is solid and perhaps long-awaited, but its true worth will depend on the realistic integration of multidimensional assessment into promotion, funding, and institutional decision-making processes. The policy raises an appropriate question, but it is yet to be determined whether India will respond to it in practice.